Wykorzystanie narzędzi marketingu bezpośredniego przejawem działalności innowacyjnej biur podróży - Michalska-Dudek, Izabela; Rapacz, Andrzej (The Implementation of Direct Marketing Tools as a Symptom of Innovative Activities Performed by Travel Agencies, 2008)
In order to enter into and keep contacts with customers purchasing their services travel agencies take advantage, more and more frequently, of the methods which facilitate direct communication with clients. The implementation of proper combination of direct marketing tools described in the article should result in the following: the ability of obtaining higher selectiveness (personalization) of offers - taking advantage of marketing data base an agency may adjust its offer to individual requirements of clients, establishing permanent relations with clients, the ability for choosing the best moment for contacting clients, ensuring privacy, since the activities in the field of direct marketing are invisible for the competition, measurability of activities in the field of direct marketing, which results from the fact that it is easy to establish the number of bookings made, the share of bookings (purchases) finalized within this number, efficiency of different communication forms with the market or purchasing behaviours of clients, the ability to carry out systematic evaluation of purchasing process and purchasing behaviours of clients. The conducted analysis results indicate that among the most popular forms of individual communication between a travel agency and a client there are catalogues and e-mails. The latter is used on a daily basis in order to make contacts with clients in case of every fourth researched travel agency.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 84-100